Increase in Interleukin-6 Levels in the Gingiva of Male Wistar Rats Induced by Porphyromonas gingivalis - Ni Wayan Arni Sardi; Wayan Putu Sutirta Yasa; Ni Made Linawati (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Interleukin-6 (IL-6) in healthy gingiva contributes to regulating the immune response and tissue homeostasis. Exposure of lipopolysaccharide (LPS) from the Porphyromonas gingivalis bacteria (P. gingivalis) in periodontal tissues can influence the role of IL-6, shifting it from a tissue homeostatic agent to a pro-inflammatory cytokine. This study aimed to determine the levels of IL-6 in the gingiva of male Wistar rats induced by P. gingivalis bacteria. Material and Methods: This research uses a posttest-only control group design. Thirty-two male Wistar rats were divided into two groups, each consisting of sixteen rats. The control group consisted of 16 male Wistar rats that were not induced with bacteria. The experimental group consisted of sixteen male Wistar rats with the induction of P. gingivalis bacteria. Results and Discussions: The results showed that the IL-6 levels in the healthy male Wistar rat group were lower than the IL-6 levels in the male Wistar rat group induced with P. gingivalis bacteria. More exposure to LPS due to the induction of P. gingivalis bacteria causes increased permeability of the gingival mucosal barrier, which can shift the tissue balance towards a pro-inflammatory state, resulting in increased production of IL-6. Conclusion: IL-6 levels increased in the gingiva of male Wistar rats induced with P. gingivalis bacteria.